INCA-M: Mexican Adaptation of the Inventory of Callous-Unemotional Traits and Antisocial Behavior - Morales-Vives, Fabia; Gómez-Herrera, Mariana; Vigil-Colet, Andreu (Frontiers in Psychology, 2020)
Callous-unemotional traits are considered to be precursors of psychopathy, and are related to behaviors such as aggression, delinquency, antisocial behavior, and bullying in adolescents. For this reason, it is important to study these traits in childhood and adolescence with appropriate and reliable instruments. The aim of the current study is to develop a Mexican adaptation of the Inventory of Callous-Unemotional Traits and Antisocial Behavior (INCA) because few questionnaires in Spanish assess these traits, and even fewer have been validated for the Mexican population. The INCA questionnaire, developed in Spain, assesses the same three factors as the ICU questionnaire (unemotional, callousness, and uncaring), and it includes an additional factor of antisocial behavior with items on challenging authority and breaking social rules. It controls two response biases: social desirability and acquiescence. We administered the Mexican adaptation, named INCA-M, to 699 adolescents aged between 12 and 18 years old. Factor analysis yielded three dimensions, because most of the items referring to uncaring and antisocial behavior loaded on a common factor, which can be explained by cultural differences. We decided to remove these items of antisocial behavior so as to maintain the same three factors assessed by the ICU questionnaire. The results suggest that the INCA-M has good psychometric properties, with high factor simplicity and good reliability. Moreover, we found the expected correlations with impulsivity and the Big Five subscales, and also with the equivalent subscales assessed by the ICU questionnaire.